(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Diabetes mellitus (DM) is a leading non-communicable chronic disease that has become a pandemic in recent decades. [1]. According to the Diabetic Endocrinology Association in 2022, diabetes is rightfully considered as one of the most common comorbid pathologies recorded in patients with COVID-19 [2]. At the same time, to date, a significant number of large RCTs, systematic reviews and meta-analyses have been published proving that the virus SARS-CoV-2 is capable of triggering a cascade of pathoimmunological reactions leading, under the influence of the multifactorial environment, to the development of type 1 diabetes mellitus [3-5].